MAIN DIRECTIONS OF MODERNIZATION OF EDUCATIONAL PROCESS IN MEDICAL UNIVERSITY - A. A. Shuldyakov; O. V. Shamsheva; I. Yu. Melnikova; M. G. Romantsov; E. P. Lyapina (Детские инфекции (Москва))
The development of the modern education system presupposes training with a high level of independence and the leading role of the student’s personality. Vocational education institutions should provide a wide range of educational services that are adequate to demands of the labor market. Methods and forms of education must be variable. Modern educational technology should be used of the as one of the most convenient ways of training.